Esan, Yıldıztepe granit ocağından parke taşı üretimi ve blok elde etme yöntemlerinin incelenmesi - Zanbak, M. Hüseyin (Fen Bilimleri Enstitüsü, 1995)
quality, energy efficiency, safety and health at the workplace and impact on the en vironment. Of course, economic factors will exert a decisive pressure on the tech nical choice. The problem of quality is today of a mayor concern in relation to the more elaborate and delicate use of the material, requiring well established technological properties, in additon, a process of more severe selection among available materials is induced by the international competition. Produced blocks are cutted, polished and packed in modern finishing plants. It is important that where do we use marble and /or granite.This is a problem which project designers come up against again and again.Unfortunately there is no simple formula or solution because the variables and criteria involved are more or less in finite. It is wise to use granite outside and marble inside.This is because materials used to outside have to be able to resist atmospheric and pollutant agents for long long periods, and in these days pollutants are ever more aggressive and seem ever more determined to ruin anything that happens to be natural and that was intended to last. More generally, materials which are used outside are usually put there for long er and have to handle more stress and shock because they are used by more people and vehicles. Marble can be used for interior furnishing and paving.lt has less resistance to wear and tear but there is a greater variety of colour available and marble tends to fit in better with a lived-in environment, it is more individual, easier to tailor to par ticular Pastes. Another, though not the last, reason for using this basic criteria for choice Is that marble's qualities of softness and colour contrasts are enhanced when the stone is polished.However, the polish on marble doesn't last as long as it does on granite, hence it is better to have it inside. But this is by no means the last word on the subject.One can perfectly well use marble outside and granite inside with excellent results. The organization of society has since time immemorial involved the develop ment of common spaces where people could get together and meet and talk. This need has been felt by every kind of society and association whether it be civil, religi ous, military, commercial, industrial, urban, rural, sportive, cultural or whatever. The inevitable result was the creation over the centuries of various shapes and styles of building which all relied on stone as the most expressive, suitable and safe material available. Every kind of building can gain in character and personality from the use of stone. Stone can be used on the outsides of buildings and in the open air in many

ways, as can be seen from a brief glance around our cities, our squares and urban landscapes. Stone materials can be used both for outside paving and inside flooring, for toughness and durability and the beauty of the effect they offer they have yet to bee- quailed by man-made materials. Stone materials are very well suited for use as inter nal and external wall claddings. Stone is extremely attractive when used for interior furnishings. It offers that final touch which gives personality and individuality to a home. Stone can be used either as cladding or flooring, or both, in kitchens and bathrooms. - xn- quality, energy efficiency, safety and health at the workplace and impact on the en vironment. Of course, economic factors will exert a decisive pressure on the tech nical choice. The problem of quality is today of a mayor concern in relation to the more elaborate and delicate use of the material, requiring well established technological properties, in additon, a process of more severe selection among available materials is induced by the international competition. Produced blocks are cutted, polished and packed in modern finishing plants. It is important that where do we use marble and /or granite.This is a problem which project designers come up against again and again.Unfortunately there is no simple formula or solution because the variables and criteria involved are more or less in finite. It is wise to use granite outside and marble inside.This is because materials used to outside have to be able to resist atmospheric and pollutant agents for long long periods, and in these days pollutants are ever more aggressive and seem ever more determined to ruin anything that happens to be natural and that was intended to last. More generally, materials which are used outside are usually put there for long er and have to handle more stress and shock because they are used by more people and vehicles. Marble can be used for interior furnishing and paving.lt has less resistance to wear and tear but there is a greater variety of colour available and marble tends to fit in better with a lived-in environment, it is more individual, easier to tailor to par ticular Pastes. Another, though not the last, reason for using this basic criteria for choice Is that marble's qualities of softness and colour contrasts are enhanced when the stone is polished.However, the polish on marble doesn't last as long as it does on granite, hence it is better to have it inside. But this is by no means the last word on the subject.One can perfectly well use marble outside and granite inside with excellent results. The organization of society has since time immemorial involved the develop ment of common spaces where people could get together and meet and talk. This need has been felt by every kind of society and association whether it be civil, religi ous, military, commercial, industrial, urban, rural, sportive, cultural or whatever. The inevitable result was the creation over the centuries of various shapes and styles of building which all relied on stone as the most expressive, suitable and safe material available. Every kind of building can gain in character and personality from the use of stone. Stone can be used on the outsides of buildings and in the open air in many - XI- ways, as can be seen from a brief glance around our cities, our squares and urban landscapes. Stone materials can be used both for outside paving and inside flooring, for toughness and durability and the beauty of the effect they offer they have yet to bee- quailed by man-made materials. Stone materials are very well suited for use as inter nal and external wall claddings. Stone is extremely attractive when used for interior furnishings. It offers that final touch which gives personality and individuality to a home. Stone can be used either as cladding or flooring, or both, in kitchens and bathrooms. - xn- quality, energy efficiency, safety and health at the workplace and impact on the en vironment. Of course, economic factors will exert a decisive pressure on the tech nical choice. The problem of quality is today of a mayor concern in relation to the more elaborate and delicate use of the material, requiring well established technological properties, in additon, a process of more severe selection among available materials is induced by the international competition. Produced blocks are cutted, polished and packed in modern finishing plants. It is important that where do we use marble and /or granite.This is a problem which project designers come up against again and again.Unfortunately there is no simple formula or solution because the variables and criteria involved are more or less in finite. It is wise to use granite outside and marble inside.This is because materials used to outside have to be able to resist atmospheric and pollutant agents for long long periods, and in these days pollutants are ever more aggressive and seem ever more determined to ruin anything that happens to be natural and that was intended to last. More generally, materials which are used outside are usually put there for long er and have to handle more stress and shock because they are used by more people and vehicles. Marble can be used for interior furnishing and paving.lt has less resistance to wear and tear but there is a greater variety of colour available and marble tends to fit in better with a lived-in environment, it is more individual, easier to tailor to par ticular Pastes. Another, though not the last, reason for using this basic criteria for choice Is that marble's qualities of softness and colour contrasts are enhanced when the stone is polished.However, the polish on marble doesn't last as long as it does on granite, hence it is better to have it inside. But this is by no means the last word on the subject.One can perfectly well use marble outside and granite inside with excellent results. The organization of society has since time immemorial involved the develop ment of common spaces where people could get together and meet and talk. This need has been felt by every kind of society and association whether it be civil, religi ous, military, commercial, industrial, urban, rural, sportive, cultural or whatever. The inevitable result was the creation over the centuries of various shapes and styles of building which all relied on stone as the most expressive, suitable and safe material available. Every kind of building can gain in character and personality from the use of stone. Stone can be used on the outsides of buildings and in the open air in many - XI- ways, as can be seen from a brief glance around our cities, our squares and urban landscapes. Stone materials can be used both for outside paving and inside flooring, for toughness and durability and the beauty of the effect they offer they have yet to bee- quailed by man-made materials. Stone materials are very well suited for use as inter nal and external wall claddings. Stone is extremely attractive when used for interior furnishings. It offers that final touch which gives personality and individuality to a home. Stone can be used either as cladding or flooring, or both, in kitchens and bathrooms.
The Research Of Block Quarrying Methods And Cobble Stone Production İn Esan Yildiztepe Granite Quarry
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1995
Keywords: Balıkesir; Granit; Parke taşları; Balıkesir; Granite; Cobble stones